Perilaku Bullying terhadap Anak Berkebutuhan Khusus di Sekolah Inklusif Kota Padang - Diffany Noriko Sakinah; Marlina Marlina (Jurnal Penelitian Pendidikan Khusus, 2018)
This article contains about the bullying behavior of children with special needs in inclusive schools in the city of Padang. This research originated from cases of bullying that afflicted A and C which were children with special needs at SMK N 7 Padang and SMP N 30 Padang.This study aims to find out how bullying behavior is carried out when carrying out bullying actions, namely the ways needed for these actions, important from bullying actions and knowing what makes sense of bullying to children with special needs in other countries.This research is a qualitative descriptive study with the research subjects being children with special needs at SMK N 7 Padang and SMP N 30 Padang. The research respondents were students and teachers at SMP N 30 Padang and SMK N 7 Padang. Collecting of data from observation, interviews and documentation studies. the processors use observation instruments, research grids, and documentation.The results of this study indicate that the forms of bullying behavior that were received by A and C were laughed at, excluded, labeled, and cheated. this happens because of the lack of understanding of students and teachers about bullying and its effects. Help or answer the school in this case to be important, because the actions you can help reduce bullying cases in schools providing inclusive education